More than skin deep: cyclic peptides as wound healing and cytoprotective compounds - Lee, Ying-Chiang J.; Javdan, Bahar; Cowan, Alexis; Smith, Keith (Frontiers in Cell and Developmental Biology, 2023)
The prevalence and cost of wounds pose a challenge to patients as well as the healthcare system. Wounds can involve multiple tissue types and, in some cases, become chronic and difficult to treat. Comorbidities may also decrease the rate of tissue regeneration and complicate healing. Currently, treatment relies on optimizing healing factors rather than administering effective targeted therapies. Owing to their enormous diversity in structure and function, peptides are among the most prevalent and biologically important class of compounds and have been investigated for their wound healing bioactivities. A class of these peptides, called cyclic peptides, confer stability and improved pharmacokinetics, and are an ideal source of wound healing therapeutics. This review provides an overview of cyclic peptides that have been shown to promote wound healing in various tissues and in model organisms. In addition, we describe cytoprotective cyclic peptides that mitigate ischemic reperfusion injuries. Advantages and challenges in harnessing the healing potential for cyclic peptides from a clinical perspective are also discussed. Cyclic peptides are a potentially attractive category of wound healing compounds and more research in this field could not only rely on design as mimetics but also encompass de novo approaches as well.